CONSUMER PREFERENCE TOWARDS THE ATTRIBUTES OF AQUAPONICS PRODUCTS AT PT. TANIKOTA - Tedjalaksana, Viorensa; Deliana, Yosini; Trimo, Lucyana (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The increasing awareness of healthy lifestyle among the public has made consumers more selective in choosing their food, particularly vegetables. Aquaponic vegetable products, which are free from pesticides, have emerged as an alternative for health-conscious consumers. This study aimed to identify the characteristics of consumers who purchase aquaponic vegetables based on product attributes at PT. Tanikota and to determine the ranking of attributes of aquaponic vegetables according to consumer preferences. The research method employed in this study was a case study, using a whole population of 70 aquaponic vegetable consumers at PT. Tanikota as the respondents. Data were analyzed using descriptive analysis of frequency distribution. The results of the study revealed that the characteristics of consumers who buy aquaponic vegetables at PT. Tanikota were generally women aged 26-35 years, holding an undergraduate degree, with 3 family dependents, employed in private sectors, and having an income range of 2,600,000-Rp 5,200,000/month. The attributes of aquaponic vegetables at PT. Tanikota were ranked based on consumer preferences, with the level of freshness of vegetables, variety of vegetables, color of vegetables, method of payment, method of purchase, physical form of vegetables, vegetable size, distance, vegetable packaging, and the price of vegetables, respectively. The lower rank of price attributes can be attributed to the lack of aquaponic vegetable cultivation in the city of Bandung, which makes it difficult for consumers to compare the prices offered by PT. Tanikota with those offered by other companies.